The U.S. Maritime Strategy and Its Effect on U.S.-- Norwegian Relations and Security - Skjostad, Odd V. (1989)
While the United States maritime strategy has a global perspective, this study focuses on operational consequences of the maritime strategy in the Norwegian Sea. It addresses both present patterns of U.S. naval operations and possible consequences of the maritime strategy in crisis and wartime. The study recognizes an increased interdependence between U.S. naval operations and the defense of North Norway and points out military strengths and weaknesses as well as political limitations in connection to these operations. The conclusion gives advice to U.S. strategic planners both on the military and political fields.